Genetic Divergence in Yardlong Bean (Vigna unguiculata (L.) Walp. Ssp. Sesquipedalis Verdc.) (Bangladesh Journal of Botany, 2012)
Genetic divergence among 13 commercial yardlong bean (Vigna unguiculata (L.) Walp. ssp. sesquipedalis Verdc.) genotypes was investigated to select the parents for hybridization using Mahalanobis D2 statistics. Cluster analysis was used for grouping 13 yardlong bean genotypes. The genotypes fall into four   clusters. Cluster III had the maximum (5) and cluster I had the minimum (1) number of genotypes. Cluster III   (D2 = 1.439) had highest intra-cluster distance and the lowest in cluster I (D2 = 0.000). The inter-cluster   divergence ranged from 4.160 to 15.515 between clusters II and III and clusters I and II, respectively. The   characteristics i.e. number of pods per plant, number of pods per cluster, days to first flowering, and   vegetable pod yield per plant contributed maximum towards divergence among yardlong bean genotypes. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11084 Bangladesh J. Bot. 41(1): 61-69, 2012 (June)